Developing co-management for conservation and local development in China’s national parks: findings from focus group discussions in the Sanjiangyuan Region - Ma, Ting; Swallow, Brent; Foggin, J. Marc; Sang, Weiguo; Zhong, Linsheng (Frontiers in Conservation Science, 2023)
Environmental protection in China has progressed significantly in the past decades, including introduction of more collaborative approaches in the management of protected areas and the establishment of a new national park system, and many milestones have been achieved. While such developments are driven largely by national and global goals, the people who are most affected are those who reside in the protected landscapes. A range of strategies have been proposed and tried in relation to local development, with many important lessons learned, yet little has been heard to date directly from the community stakeholders themselves. In this study we report on feedback and recommendations received from focus group discussions in vicinity of China’s first national park, Sanjiangyuan, regarding lived experiences of “community co-management” by Tibetan herders and local officials. Overall, the most recent National Park model is deemed successful, albeit with some notable perceived limitations. Focus group discussions participants recommend more balanced compensation opportunities including for communities living outside but in close proximity to the park, eased restrictions on ecotourism, provision of public services for communities in the park (especially waste management and health care) and establishing a more effective compensation or insurance system to offset economic losses due to wildlife damage.